Recognizing The Meta-Function Of News Item - Achmad Hilal Madjdi; Agung Dwi Nurcahyo (Lembaga Penelitian Universitas Muria Kudus, 2014)
Language is a means of communication which has two main systems, i.e. system of form and meaning. The meanings realized by language are textual and contextual meaning. Therefore, language cannot be separated from its context of use. This study investigates how context of situation influences the use of language, more specifically, in the perspective of language meta-function concept. The language that is used in news items, like daily newspaper also has certain characteristic which is influenced by the author (the writer) and the socio- political situation of the society. The objective of the research is to describe how ideational meaning is realized in the Jakarta Post headline news on the fuel increasing issue. The research is a text analysis by using Systemic Functional Linguistics (SFL) theory which cover (1) the classification imbedded in the phase sequences, (2) the sequences of events in the phases, (3) The sequences of events of the Jakarta Post Headline News on fuel price- increasing issue in April 2012, which are specifically concerned with the process and (4) how people and thing are attributed in the text.